Determination of bone age and evaluating the applicability of Greulich-Pyle standards among the Turkish children - Özgül, Esra; Yücel, Aylin; Kaya, Furkan; Koca, Serkan Bilge; Ertekin, Ayşe (Journal of Surgery and Medicine, 2022)
Background/Aim: Bone age (BA) is important in the diagnosis and follow-up of pediatric growth disorders. Skeletal maturation can vary according to the geographical region and climate. The goal of this study is to investigate whether Greulich-Pyle (GP) method is suitable for detecting BA for Turkish children for all age groups and both genders. Methods: In our retrospective cohort study, the roentgenograms of all pediatric patients who visited the pediatrics or pediatric endocrinology outpatient clinics and underwent left hand and wrist radiographs for suspicious trauma or BA determination were examined with reference to the GP atlas. Patients without evidence of chronic disease or growth disorders with body size and weight values between the 25th-75th percentile were included. Poor quality roentgenograms were excluded. Results: Radiographs of 665 patients were analyzed and 310 (161 boys and 149 girls, age range 13-203 months) patients were included. The rate of concordant BA with CA was significantly higher in the children above 120 months of age and low BA was significantly higher among the children aged 120 months or below (P<0.001). The rate of concordant BA with CA was significantly higher among girls and low BA was significantly higher among boys (P=0.014). Among patients aged 120 months or below, low BA was significantly higher in the boys (P<0.001). There were no significant differences between the boys and girls aged 120 months and above (P=1.000) Conclusion: Although widely used in the determination BA, local studies on the accuracy and reliability of the GP method are insufficient in less developed countries. The accuracy of this method in Turkish children, especially boys under the age of 10 years, is controversial, and correct standards should be developed.